HUBUNGAN CITRA TUBUH DENGAN GANGGUAN PERILAKU MAKAN PADA REMAJA PUTRI PENGGUNA INSTAGRAM - Ni Kadek Novi Ariani; Kadek Eka Swedarma; I Kadek Saputra (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
The use of Instagram as a social media can have an indirect negative impact on adolescents. Obsession with Instagram celebrities that have an ideal body shape can lead to adolescent dissatisfaction with their body image. This can trigger eating behavior disorders in adolescents. This study aimed to identify the relationship between body image and eating behavior disorders in adolescent girls using Instagram at SMA (Senior High School) ??Saraswati 1 Denpasar. This research used the descriptive correlation design with a cross-sectional approach. The amount of the sample is 150 young women in grade X and XI majoring in MIA and IIS which were selected using disproportionate stratified random sampling technique. Body image was measured using the MBSRQ-AS 34, and eating disorders were measured using the EAT-26 questionnaire. The results of this study showed most of the respondents have moderate body image (51.3%) and the majority have a risk of eating disorder (54.7%). Based on spearman rank analysis showed the p value is 0.000 (p 0.05) with a correlation coefficient of 0.620. Instagram can be a platform that causes dissatisfaction with body image leading to eating behavior disorders so that young women need to evaluate and have good information regarding their body image so as not to cause eating behavior disorders.